Analysis of Javanese Speech Acts in families in Sawit Sebrang subdistrict, Langkat Regency - Supriadi (The Seall Journal, 2023)
This study examines Javanese speech acts within the context of the familial environment in Langkat Regency's Sawit Sebrang District, with an emphasis on locutionary, illocutionary, and perlocutionary functions. This study employs qualitative descriptive methods to examine oral conversations with neighbors, family members, and local residents. The results demonstrate the use of a variety of speech acts in various contexts, including discussions of geriatric oil palm plantations and education-related financial issues. Locutionary speech acts are distinguished from illocutionary speech acts by the speaker's intent to convey information and anticipation of a particular response; the former occurs when the speaker merely imparts factual information without any particular intention. Perlocutionary speech acts occur when the utterance has a substantial impact on the behavior of the recipient. This study underscores the significance of cultural awareness, linguistic diversity, and local expressions when attempting to decipher the intended significance of Javanese speech acts. Cultural elements and colloquial language significantly influence the efficacy of communication within the familial setting. An examination of the Sawit Sebrang family's Javanese speech acts offers significant insight into the intricate nature of communication within this particular cultural milieu. Gaining comprehension of these speech acts expands our understanding of communication practices and provides tangible examples of how to implement effective communication strategies. Keywords: Speech act, Javanese, Family.